Study of the zirconium and silicon homovalent dopants insertion on the structure and bandgap energy of titanium dioxide powders - Garcia, Hiana Muniz; Carli, Eduardo Felipe De; Cruz, Natali Amarante da; Stropa, Jusinei Meireles [UNESP]; Favarin, Lis Regiane Vizolli [UNESP]; Junior, Amilcar Muchulek [UNESP]; de Oliveira, Lincoln Carlos Silva [UNESP]; Cavalheiro, Alberto Adriano (Trans Tech Publications, 2018)
The reconstructive transformation occurring during the anatase-to-rutile phase transition can be observed through adequate techniques such as Thermal Analyses and Z-ray diffractometry followed by structural refinement. The typical photonic properties of titanium dioxide photocatalysts depend on the anatase structure and how the modifiers can provide their performance enhancement. In the present work, we investigate the structural effects caused by the simultaneous homovalent modification on the anatase structure in order to understand the mechanisms of the anatase-to-rutile phase transition in terms of the atomic coordinates and the lattice parameters. The refined structures along the calcination temperature from 500 to 900 ºC suggest the oxygen bonds are strongly affected in unmodified anatase in order to destroy and rebuilt the crystal structure and lead to the rutile phase formation above 700 ºC, unless some modifier pairs stabilize them.
Keywords: Rietveld; Sol-Gel; Thermal Analysis; Titanium Dioxide Anatase